2016
DOI: 10.18632/oncotarget.12664
|View full text |Cite
|
Sign up to set email alerts
|

Filamin A interacting protein 1-like expression inhibits progression in colorectal cancer

Abstract: Filamin A interacting protein 1-like (FILIP1L) expression, which is decreased in various cancers, may inhibit carcinogenesis. In this study, we evaluated the effects of FILIP1L on oncogenic behavior and prognosis in colorectal cancer. siRNA-mediated FILIP1L knockdown enhanced tumor cell migration and invasion and inhibited apoptosis and cell cycle arrest in COLO205 cells. pcDNA-myc vector-mediated FILIP1L overexpression suppressed tumor cell migration and invasion and induced apoptosis and cell cycle arrest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…A previous study showed that there is a positive relationship between FLNa and VEGF in patients with lung cancer (43). However, a separate study emphasized that FLNa interacting with other proteins inhibits CRC progression (44), indicating that FLNa may represent a novel cancer-suppressor gene for treating colorectal adenocarcinoma. Thus, the current literature suggests a dual role for FLNa and complex underlying mechanisms in various types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that there is a positive relationship between FLNa and VEGF in patients with lung cancer (43). However, a separate study emphasized that FLNa interacting with other proteins inhibits CRC progression (44), indicating that FLNa may represent a novel cancer-suppressor gene for treating colorectal adenocarcinoma. Thus, the current literature suggests a dual role for FLNa and complex underlying mechanisms in various types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, FILIP1L has been shown to have a role in inhibition of WNT signaling pathway, a pathway implicated in colorectal cancer and metastasis as well as in cellular invasion in an ovarian cancer model and colon cancer cell lines . Consistent with these results, another study showed that reduced levels of this protein in colorectal tumors were associated with reduced overall survival times of patients . While it is currently unknown whether these INDELs/CNVs have biological effects on the corresponding genes (and hence, have direct effects on the disease progression and risk of relapse in colorectal cancer), it is quite possible as a large number of noncoding sequences in the human genome contain regulatory elements .…”
Section: Discussionmentioning
confidence: 70%
“…In addition, Filamin A interacting protein 1-like (FILIP1L), which was reported to be down-regulated in EOC and negatively correlated with EOC tumor stages, chemoresistance, and patient survival [69], has been found to induce β-catenin degradation [69, 72]. While the underlying mechanism by which FILIP1L inhibits β-catenin has not been determined in EOC, knockdown of FILIP1L in colon cancer cell lines led to an increase in phosphorylated AKT and GSK-3β and a decrease in phosphorylated β-catenin levels, suggesting that FILIP1L may promote β-catenin degradation by inhibiting AKT and thereby increasing GSK3β activity [73]. Finally, RAB14, a member of the RAS small G-protein superfamily [68, 74], has also been reported to be upregulated in EOC tissues and cell lines [68].…”
Section: Introductionmentioning
confidence: 99%